Non-Technical Skill Level of Electrical Engineering Undergraduates Using the Rasch Measurement Model - Najwa Azmi, Aini; Kamin, Yusri; Khair Noordin, Muhammad; Nabil Md. Nasir, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
Currently, employers seek employees, especially fresh graduates, to have good non-technical skills. They complain that the engineering students lack non-technical skills but are good at technical skills. Thus, it is the responsibility of the university to equip students with enough non-technical skills before entering a competitive workplace. Industrial training provides an opportunity for students to develop their non-technical skills. This study determines the non-technical skills level of electrical engineering undergraduates using the Rasch Measurement Model (RMM). The questionnaire was distributed to 326 electrical engineering undergraduates who had undergone their industrial training at seven public universities in Malaysia after the questionnaire had passed the reliability and validity tests. The finding shows that the level of overall non-technical skills after industrial training is at moderately low. When the non-technical skills are looked at as individual skills, the findings show that communication skills, critical thinking, problem-solving skills, and teamwork skills are at moderately low and low levels, respectively. However, other skills like entrepreneurial skills, engineering ethics, lifelong learning, and computing skills are at a very high level. To make sure the students can develop those moderately low- and low-level skills, the issues in the industrial training involving placement, training duration, type of training/task given, and assessment should be reduced to make sure students can gain the most valuable training, which benefits all the parties who are industries, universities, and students.